The Roles of Exosomes in Regulating Hair Follicle Growth - Cheng M; Ma C; Chen HD; Wu Y; Xu XG (Dove Medical Press, 2024)
Ming Cheng,1,2 Cong Ma,1- 3 Hong-Duo Chen,1,2 Yan Wu,1,2 Xue-Gang Xu1,2 1Department of Dermatology, The First Hospital of China Medical University, Shenyang, 110000, People's Republic of China; 2Key Laboratory of Immunodermatology, Ministry of Education and NHC; National Joint Engineering Research Center for Theranostics of Immunological Skin Diseases, Shenyang, 110000, People's Republic of China; 3Department of Dermatology and Sexually Transmitted Diseases, The First Hospital of Inner Mongolia University for Nationalities, Tongliao, 028000, People's Republic of ChinaCorrespondence: Xue-Gang Xu; Yan Wu, Department of Dermatology, The First Hospital of China Medical University, Shenyang, 110000, People's Republic of China, Email xuxuegang2749290@163.com; jlwuyan@126.comAbstract: Alopecia is considered a widespread yet troubling health issue, with limited treatment options. As membranous structures derived from cells carrying proteins, nucleic acids and lipids, exosomes functionally medicate intercellular communication and alter the responses of recipient cells, resulting in disease restraint or promotion. Exosomes have broad prospects in diagnosis and treatment of diseases. Studies using animal models and at the cellular level have clearly shown that exosomes from several types of cells, including dermal papilla cells and mesenchymal stem cells, have a notable capacity to promote hair growth, suggesting that exosomes may provide a new option to treat alopecia. Here, we present a thorough review of the most recent progress in the application of exosomes to hair growth.Keywords: exosome, hair follicle, alopecia